Analysis of drivers of customer satisfaction to inform customer centricity: Banking sector perspectives - Hillary Mulindi; Hesborn N. Nyagaka; Kiplangat Josea Cheruiyot; Christine Onyango; Samuel Tiriongo (Kenya Bankers Association (KBA), 2024)
Intense competition from alternative financial service providers and evolving customer expectations have presented formidable challenges to the banking sector's quest for customer retention and profitability. On this account, this paper delves into the dynamics of customer satisfaction in the banking sector with a view to inform customer centricity. Using the banking sector customer satisfaction survey data and multinomial logit, the study shows that bank customers with multiple bank accounts with other banks have a low likelihood of being dissatisfied while the human interaction is still valued by bank customers, even though banks are quickly automating their processes. Moreover, prompt customer complaint resolution leads to higher satisfaction. The key policy issues arising from the study is the need for banks to develop a robust complain handling strategies and to tailor their products to the customers needs.
Keywords: 330; Kundenzufriedenheit; Kundenbindung; Bank; Kenia